2020
DOI: 10.3390/molecules25225279
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Effects of Pterosin B on Ang II-Induced Cardiomyocyte Hypertrophy

Abstract: Pathological cardiac hypertrophy is characterized by an abnormal increase in cardiac muscle mass in the left ventricle, resulting in cardiac dysfunction. Although various therapeutic approaches are being continuously developed for heart failure, several studies have suggested natural compounds as novel potential strategies. Considering relevant compounds, we investigated a new role for Pterosin B for which the potential life-affecting biological and therapeutic effects on cardiomyocyte hypertrophy are not full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Ang II has been closely related to remodeling, which acts mainly via AT1 R in the animal and human cardiovascular systems. PKCs-EKR1/2-NFκB-NLRP3-IL1β pathway signaling cascades have been shown to promote Ang II-induced cardiomyocyte hypertrophy in H9c2 cells through AT1 R, RAGE, and NADPH oxidase inhibition ( Lee et al, 2020 ). Soluble RAGE (sRAGE) was demonstrated as a decoy receptor for RAGE in Ang II-induced cardiomyocyte hypertrophy using in vivo and real-time 9.4T MR imaging ( Heo et al, 2019 ).…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II has been closely related to remodeling, which acts mainly via AT1 R in the animal and human cardiovascular systems. PKCs-EKR1/2-NFκB-NLRP3-IL1β pathway signaling cascades have been shown to promote Ang II-induced cardiomyocyte hypertrophy in H9c2 cells through AT1 R, RAGE, and NADPH oxidase inhibition ( Lee et al, 2020 ). Soluble RAGE (sRAGE) was demonstrated as a decoy receptor for RAGE in Ang II-induced cardiomyocyte hypertrophy using in vivo and real-time 9.4T MR imaging ( Heo et al, 2019 ).…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%
“…Soluble RAGE (sRAGE) was demonstrated as a decoy receptor for RAGE in Ang II-induced cardiomyocyte hypertrophy using in vivo and real-time 9.4T MR imaging ( Heo et al, 2019 ). In addition to RAGE, it has been noted that Toll-like receptor 2 (TLR2)- and TLR4-dependent pathways are stimulated by Ang II in cardiac dysfunction, fibrosis and hypertrophy ( Lee et al, 2020 ). TLR4 is involved in the upregulation of monocyte chemoattractant protein (MCP-1), IL-6, and ROS ( Matsuda et al, 2015 ).…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%
“…It has been reported that the activation of the nuclear factor-kappa B (NF-κB) signaling pathway is required for the hypertrophic growth of cardiomyocytes [ 22 ]. NF-κB is an oxidative stress-sensitive transcriptional factor for inflammation, immune response, and cell growth; its activity is stimulated by several hypertrophic agonists, such as endothelin-1 and Ang II [ 22 , 23 , 24 ]. Additionally, the upregulation of NF-κB—together with the excessive expression of pro-inflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α)—associated with cardiac hypertrophy has been observed in L-NAME hypertensive rats [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II receptor blockers (ARBs) (candesartan cilexetil, eprosartan, irbesartan, losartan, olmesartan medoxomil, telmisartan, valsartan, etc.) generally have similar indications as ACEI, but not identical [77][78][79]. Their mechanism of action is different: ARBs bind and block the angiotensin receptors, mainly AT1 receptor (angiotensin II receptor type 1), and ARBs stimulate the release of renin, with a consequent increase in AngII (angiotensin II) plasmatic levels [77].…”
Section: Angiotensin II Receptor Blockersmentioning
confidence: 99%